DE NOVO SYNTHESIS OF A PLASMID CONTAINING THE Chlamydia abortus OUTER MEMBRANE PROTEIN A (OMP A) GENE - Zhumabek , A.T.; Zhylkibayev , А.А.; Kairzhanova , А.D.; Eskendirova , S.Z.; Manabayeva , Sh.А.; Shevtsov , А.B. (Eurasian Journal of Applied Biotechnology, 2017)
Chlamydia is a significant disease in animals and birds. Chlamydia results in important economic damage by causing the death of animals, pathology of reproductive organs, spontaneous abortion, and the bearing of dead offspring. The prevalence of chlamydia pathogens in nature among domestic and wild animals, including birds, presents a constant threat for people professionally engaged in agriculture. Great attention is paid to diagnosis when performing anti-epizootic activities associated with the prevention and elimination of chlamydia. According to the instructions of the World Organization for Animal Health (OIE), cell culture is the main diagnostic method for the identification of chlamydia causative agents. However, the duration and laboriousness of cell culture methods, along with the risk of staff infection, make laboratory diagnostics very difficult. In guidance to OIE diagnostic tests and vaccines prescribed the use of more than five modifications of PCR test systems for the diagnosis of chlamydia. A large proportion of animals with pathological Chlamydia have Chlamydia abortus. Here, we describe how we designed and synthesized a plasmid containing the conserved C. abortus outer membrane protein A (ompA) gene. After two-stage PCR synthesis, we obtained a 357bp long amplicon consisting of the C. abortus ompA gene flanked by BamHI and SacI restriction sites. The ompA gene was then cloned into thepUC57 plasmid, which was subsequently used to transform competent cells. Sequencing of transformant clones resulted in the identification and selection of a clone containing the ompA gene. The plasmid vector described here, containing the C. abortus ompA nucleotide sequence, can be used as a positive control in the development of PCR test systems for the diagnosis of animal chlamydiosis and for testing the sensitivity of PCR protocols.